Melampaui Dikotomi Barat dan Timur: Tipologi Kesarjanaan Non-Muslim dalam Studi Islam Kontemporer - Majdi, Ahmad Labib; Chairunnisa, Madiha Dzakiyyah (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
This article aims to map the typology of non-Muslim scholarship in contemporary Islamic studies by examining its institutional position within American and European universities, the fields and methodologies it employs, and the theoretical frameworks it produces. This aim arises from a critique of the stigmatized and reductionist view held by some Muslim (insider) scholars who regard non-Muslim (outsider) scholarship as a monolithic intellectual bloc. This study adopts a library research design with literature selection criteria that include the use of English- and Indonesian-language sources as dominant academic languages; a publication range from the 1980s to the 2020s as a representation of contemporary developments; the prioritization of seminal primary works and relevant secondary sources; and a focus on literature addressing Islamic studies methodologies, the insider–outsider approach, and the evolution of the revisionist school. Data were analyzed through a qualitative, descriptive-explanatory approach consisting of three methodological steps: data reduction, data presentation, and data interpretation and conclusion drawing. The findings reveal that non-Muslim scholarship in Islamic studies is not monolithic but can be identified through four typologies: descriptive-traditionalist, historical-critical-traditionalist, historical-critical-revisionist, and skeptical-revisionist. These findings affirm that works and ideas from non-Muslim scholars that may appear negative should be understood as a consequence of specific methodological choices. Consequently, rejecting particular theses advanced by non-Muslim scholarship does not necessarily entail the arbitrary rejection of its broader epistemological and methodological frameworks.